2006
DOI: 10.1161/01.hyp.0000218586.21932.3c
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Hypertension

Abstract: G iven the social significance of alcohol worldwide it is not surprising that there is continuing strong interest in the relation between alcohol and hypertension. Recent research continues to address unresolved questions concerning the balance between the medical hazards and the cardiovascular benefits of alcohol, the possible significance of different types of beverage, the role of different drinking patterns for cardiovascular morbidity and mortality, and mechanisms underlying the pressor effects of ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 33 publications
7
60
1
1
Order By: Relevance
“…22 In women, we found a possible J-shaped association in which light-to-moderate alcohol consumption modestly lowered hypertension risk, whereas heavier consumption of Ն4 drinks per day significantly increased hypertension risk. This association largely , and parental history of MI Ͻ60 years (no or yes).…”
Section: Discussionmentioning
confidence: 67%
“…22 In women, we found a possible J-shaped association in which light-to-moderate alcohol consumption modestly lowered hypertension risk, whereas heavier consumption of Ն4 drinks per day significantly increased hypertension risk. This association largely , and parental history of MI Ͻ60 years (no or yes).…”
Section: Discussionmentioning
confidence: 67%
“…Almost all of them have shown that habitual drinkers have a higher BP Alcohol, blood pressure and cardiovascular disease Y Kawano and higher prevalence of hypertension than nondrinkers. [1][2][3][54][55][56][57][58] These associations have been observed regardless of race, gender, age and the type of alcohol ( Figure 2). Although some studies suggest the presence of a threshold regarding the pressor effect of alcohol, 59,60 the relationship between the level of alcohol consumption and BP is usually linear.…”
Section: Actions Of Alcohol On Water and Electrolyte Metabolismmentioning
confidence: 99%
“…It has been estimated that about 10% of hypertension in the general population can be attributed to alcohol. [1][2][3] The relationship between alcohol and BP seems to be independent of confounding variables. Increases in the body weight and abdominal fat associated with alcohol consumption, however, may have a role in alcohol-related hypertension.…”
Section: Actions Of Alcohol On Water and Electrolyte Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular alcohol intake has been reported to be associated with a doserelated increase in blood pressure, 15 and some studies have suggested that the increase in blood pressure due to alcohol intake is a risk factor for cardiovascular events. 3,4,15,16 Therefore, the inconsistent findings with regard to the relationship between alcohol intake and vascular damage might be attributable, at least in part, to the differences in blood pressure levels of the study subjects. Recently, we showed that even increased blood pressure (X130/85 mm Hg) levels are associated with accelerated arterial stiffening.…”
Section: Introductionmentioning
confidence: 99%